2023
DOI: 10.1038/s41598-022-24002-1
|View full text |Cite
|
Sign up to set email alerts
|

Low thigh muscle strength in relation to myosteatosis in patients with type 2 diabetes mellitus

Abstract: This study aimed to investigate the association of thigh muscle fat infiltration by quantitative MRI with muscle strength in patients with type 2 diabetes mellitus (T2DM). Seventy T2DM patients and sixty control subjects (71 males; age: 52 ± 8 years) underwent 3.0T MRI and isokinetic muscle strength measurements to obtain the skeletal muscle index (SMI), intermuscular adipose tissue (IMAT) proton density fat fraction (PDFF), intramuscular fat (IMF) PDFF, peak torque (PT) and total work (TW) of knee extensors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 37 publications
(43 reference statements)
1
8
0
Order By: Relevance
“…In the same study, among the subjects with a BMI < 25 mg/kg 2 , higher rates of intermuscular fat and visceral abdominal fat were linked to higher levels of fasting insulin [ 38 ]. The latter finding was confirmed in a recent study, in which the presence of myosteatosis was associated with insulin resistance in patients with T2DM, and this effect was more significant in older T2DM patients [ 39 ]. Interestingly, in patients with inflammatory bowel disease, although myosteatosis did not increase overall morbidity and mortality, it was associated with a higher postoperative morbidity following bowel resection [ 40 ].…”
Section: Discussionsupporting
confidence: 64%
“…In the same study, among the subjects with a BMI < 25 mg/kg 2 , higher rates of intermuscular fat and visceral abdominal fat were linked to higher levels of fasting insulin [ 38 ]. The latter finding was confirmed in a recent study, in which the presence of myosteatosis was associated with insulin resistance in patients with T2DM, and this effect was more significant in older T2DM patients [ 39 ]. Interestingly, in patients with inflammatory bowel disease, although myosteatosis did not increase overall morbidity and mortality, it was associated with a higher postoperative morbidity following bowel resection [ 40 ].…”
Section: Discussionsupporting
confidence: 64%
“…Diabetic myopathy is documented to be associated with reduced muscle mass and appendicular muscle strength [ 113 , 114 ]. Andersen et al [ 115 ] observed T2D-associated muscle strength loss around the ankle and knee joints.…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…Andersen et al [ 115 ] observed T2D-associated muscle strength loss around the ankle and knee joints. Studies document a positive correlation between reduced thigh muscle strength, muscle ectopic fat deposition, and insulin resistance in T2D patients [ 114 ]. Furthermore, age in T2D patients was associated with muscle ectopic fat and decreased muscle strength [ 114 ].…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 99%
See 2 more Smart Citations